2016
DOI: 10.1007/s10815-016-0776-3
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of IVF-contaminated blastocysts with removal of the zona pellucida resulted in live births

Abstract: Purpose Bacterial contamination may cause loss or damage to cultured oocytes or embryos, resulting in cancelation or delaying of a fresh embryo transfer. While live births have been reported following the transfer of embryos contaminated with yeast, very little information is available on how to handle embryos with bacterial contamination. We report two cases of successful pregnancy in patients with bacterial contamination of embryo culture dishes. Methods We retrospectively reviewed 878 oocyte retrievals perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The viability of IVF embryos, in turn, depends on the composition of embryo culture media and physical environmental factors applied in embryo culture. At the same time bacterial contamination of gamete samples used in ART may impair the embryo culture environment, causing damage to or even loss of cultured oocytes and embryos [1].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of IVF embryos, in turn, depends on the composition of embryo culture media and physical environmental factors applied in embryo culture. At the same time bacterial contamination of gamete samples used in ART may impair the embryo culture environment, causing damage to or even loss of cultured oocytes and embryos [1].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that when the environmental contamination of the IVF culture room leads to contamination of the embryo culture medium, it is feasible to take measures such as strengthening the daily rapid flushing of the culture medium and reducing blastocyst culture as remedial treatment. In addition, there are other methods, such as the removal of the zona pellucida of contaminated frozen blastocysts [24]. However, the present study has some limitations.…”
Section: Discussionmentioning
confidence: 86%
“…In 1 other report, Shu et al. ( 10 ) removed the ZP of contaminated frozen blastocysts, which led to successful clinical pregnancies after the transfer of ZP-free blastocysts that were previously contaminated during IVF culture. However, the removal of the ZP in that study was not done on the day the contamination was discovered but right before embryo transfer.…”
Section: Discussionmentioning
confidence: 99%